MAPPING THE SUSCEPTIBILITY OF LODGEPOLE PINE FOREST TO MOUNTAIN PINE BEETLE ATTACK IN COLORADO, USA - Quang Anh, Ha (Journal of Forestry Science and Technology, 2017)
Lodgepole pine forest (LPP) is common forest type in Colorado. It has been attacked by many kinds of beetle and disease mostly mountain pine beetle (MPB). Forest structure and climate condition are considered as two main factors that strongly influence to LPP by MPB. In order to evaluate vulerable levels of LPP to MPB in Colorado, the pine susceptibility index (PSI) was generated from forest characteristics such stand age (A), diamter at breat height (DBH), basal area (BA) and tree density (SPH). Maps of susceptibility of this foret type based on forest age, basal area, tree density and combination of all stand structure factors were created.